2013
DOI: 10.5762/kais.2013.14.1.336
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spinal Decompression Combined with Therapeutic Modalities for Patients with Lumbar Radiculopathy

Abstract: The purpose of the present study was to determine the effect of 4 weeks course of motorized spinal decompression delivered via SpineMT(mobilization & traction) combined with therapeutic modalities on the treatment of patients with lumbar radiculopathy(LRP). A total of 15 patients with LRP (mean age, 36.63 years; age range 20-50years) participated in this study. 4 weeks course of spinal decompression delivered via SpineMT combined with therapeutic modalities was delivered to the patients for 6 days per week for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Many studies today are performed in patients with herniation of intervertebral disc [6][7][8][9][10][11]. However, there are no studies that statistically analyze the treatment effects of general Korean medicine treatments like acupuncture, moxibustion, cupping, and nonsurgical spinal decompression treatment for herniation of cervical and lumbar intervertebral discs considering demographic characteristics, location of the symptoms, and its treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies today are performed in patients with herniation of intervertebral disc [6][7][8][9][10][11]. However, there are no studies that statistically analyze the treatment effects of general Korean medicine treatments like acupuncture, moxibustion, cupping, and nonsurgical spinal decompression treatment for herniation of cervical and lumbar intervertebral discs considering demographic characteristics, location of the symptoms, and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…By continuously increasing traction force on the precise affected area, the internal pressure in the intervertebral disc decreases to negative pressure state, which may result in a therapeutic effect [5]. Published studies on decompression treatment include statistical analysis of the effect before and after treatment [6,7], a retrospective control study with Western medicine treatment [8], prospective controlled trials with Western medicine treatment [9,10], and a retrospective control study with Korean medicine [11]. However, a study that statistically compares the effect of decompression treatment with that of general Korean medicine treatment on both cervical and lumbar herniated intervertebral disc has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Gionis and Groteke10 ) reported that 89% of 229 patients with symptoms associated with herniated intervertebral discs showed improvements when they underwent spinal decompression therapy for six weeks. According to Ma et al11 ) , there was a statistically significant difference in changes in the straight leg raising test based on intervention periods when spinal decompression therapy with a therapeutic modality was applied to patients with herniated intervertebral discs for four weeks. In the present study, both groups also showed statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Routine physical therapy treatment included mild stretching of tight muscles and nerves, core stabilization exercises [ 61 ], ergonomic and postural awareness, as well as the pain relief modalities [ 30 , 62 , 63 ], i.e., TENS (Pre-Programmed Dual Channel TENS 120Z; ITO CO., LTD. Japan), ultrasound (US Pro 2000, USA) and hot pack. The TENS was applied in a conventional mode for 15 min at a high frequency of 70 Hz and wavelength of 100 microseconds [ 63 ] by placing two 40 × 40 mm electrode sets cross arranged on each side of the lumbosacral spine [ 64 ]. The ultrasound was applied over the painful lumbosacral area with circular movements of the probe head for 5 min using the intensity of 1.3 W/cm2 and frequency of 1 MHZ in continuous mode [ 63 – 65 ].…”
Section: Methodsmentioning
confidence: 99%